13C MAS NMR: A METHOD FOR STUDYING CO2 SPECIATION IN GLASSES - Kohn S.C.; Dupree R.; Brooker R.A. (My University, 1991)
13C-enriched glasses of albite, nepheline, and sodamelilite compositions were quenched from melts at 1350–1625°C and 10–35 kb, and studied using 13C and 27A1 MAS NMR. Distinct resonances for molecular CO2 and carbonate groups were observed in 13C spectra for a variety of albite glasses, whereas nepheline and sodamelilite glasses contained carbonate groups only. Two distinct carbonate groups were observed in glasses of both albite and nepheline compositions. Preliminary data on the effect of H2O and on carbon speciation in albite glasses suggest that the CO32− :CO2 ratio is increased in the presence of water, and that molecular CO is present under reducing conditions. 27Al spectra for albite and nepheline glasses show that CO2 dissolution is not accompanied by a [4]Al to [6]Al coordination change